The impact of polymer selection and dose on the incorporation of ballasting agents onto wastewater aggregates. (1st March 2020) - Murujew, Olga; Geoffroy, Jordan; Fournie, Emeline; Socionovo Gioacchini, Elisa; Wilson, Andrea; Vale, Peter; Jefferson, Bruce; Pidou, Marc
Abstract: Ballasted flocculation is an efficient high-rate sedimentation process getting more attention as an advanced P removal technology for levels below 0.1 mg/L. The process is well-known yet only very few studies have investigated the interactions, within the matrix of wastewater, of coagulant, polymer and ballast, especially when it comes to polymer doses and types which are, in the industry, rather based on recommendations than scientific evidence. In this work, the impact of anionic and cationic polymers has been investigated on P removal and floc properties. Anionic polymers showed to be superior to cationic ones when it comes to P removal and doses even as low as 0.01 mg/L yield better results than coagulant alone. There appears to be a "best-case" floc size with which very good P removal (>90%) can be achieved and flocs of sufficient strength can be generated. Highlights: Wastewater tertiary ballasted flocculation removes phosphorus to very low levels. Polymers do not act as the primary precipitating agent for phosphorus removal. Polymers provide effective incorporation of the ballast into the coagulant flocs. Large molecular weight linear anionic polymers are best for ballasted flocculation.